Advances in gut-lung axis research: clinical perspectives on pneumonia prevention and treatment - Ye, Fang; Li, Linnan; Wang, Jiao; Yang, Hongfeng (Frontiers in Immunology, 2025)
In recent years, the study of the interaction between gut microbiota and distant organs such as the heart, lungs, brain, and liver has become a hot topic in the field of gut microbiology. With a deeper understanding of its immune regulation and mechanisms of action, these findings have increasingly highlighted their guiding value in clinical practice. The gut is not only the largest digestive organ in the human body but also the habitat for most microorganisms. Imbalances in gut microbial communities have been associated with various lung diseases, such as allergic asthma and cystic fibrosis. Furthermore, gut microbial communities have significant impacts on metabolic function and immune responses. Their metabolites not only regulate gastrointestinal immune systems but may also affect distant organs such as the lungs and brain. As one of the most common types of respiratory system diseases worldwide, pulmonary infections have high morbidity and mortality rates. Pulmonary infections caused by immune dysfunction can lead to gastrointestinal problems like diarrhea, further resulting in imbalances within complex interactions that are associated with abnormal manifestations under disequilibrium conditions. Meanwhile, clinical interventions can significantly modulate the composition of gut microbiota, and alteration in gut microbiota may subsequently indicate susceptibility to pulmonary infections and even contribute to the prevention or regulation of their progression. This review delves into the interaction between gut microbiota and pulmonary infections, elucidating the latest advancements in gut-lung axis research and providing a fresh perspective for the treatment and prevention of pneumonia.